IMPLEMENTASI KONSEP AMANAH AL-MAWARDI DALAM PENGAWASAN PEMBANGUNAN DI KOMISI 4 DPRD KOTA MEDAN - Alya Qais Tsaabitah; Marzuki (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
The oversight function of the regional house of representatives holds a crucial essence in ensuring development accountability, yet its field implementation frequently encounters obstacles regarding transparency and closed documentation management. The academic anxiety in this research stems from the phenomenon of the degradation of political representation values, where strategic documents resulting from legislative oversight are often reduced merely to administrative archives justifying operational budget disbursements. This study aims to critically analyze the mechanism of infrastructure development oversight by Commission 4 of the Medan City DPRD, dismantle accountability constraints within the legislative documentation system, and offer a solution formulation based on Islamic political ethics through the manifestation of Al-Mawardi's Amanah concept. Employing a descriptive qualitative method, primary data collection was conducted through intensive participant observation during an internship at the council's secretariat, which included compiling Hearing Meeting (RDP) files and recapitulating working visit reports, then combined with literature studies. The field findings indicate that Commission 4's oversight has actually operated procedurally, evidenced by the intensity of working meetings and field inspection mobility, such as the review of the Green Open Space (RTH) policy in Aceh. Nevertheless, there is an acute accountability gap where these strategically valuable documents do not provide substantial openness access for the public. The conclusion of this study asserts that the internalization of Al-Mawardi's Amanah pillars can serve as an ethical anchor to reform documentation governance into a transparent system, returning the council's function to the orientation of public welfare, and mitigating the crisis of public distrust.